Pengaruh Latihan Fleksibilitas Split Terhadap Ketepatan Tendangan Sabit pada Atlet Pencak Silat Perguruan Padjadjaran Cimande Kuningan - Hilmi Aisyah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This study aims to determine the effect of split flexibility training on the accuracy of the sickle kick with the problems found in Padjadjaran Cimande Kuningan pencak silat college athletes when practicing and competing using the sickle kick are still ineffective, therefore the author wants to research to find out whether there is an effect of split flexibility training on the accuracy of the sickle kick in Padjadjaran Cimande pencak silat college athletes Brass. The method used is experimental research with a research design using a pre-experimental design one group pre-test and post-test. The sample of this study is athletes from the Padjadjaran Cimande Kuningan pencak silat school with a total of 10 people. The sampling technique uses purposive sampling. The instrument used was a 10-time sickle kick accuracy test. This study uses data analysis techniques using SPSS, data normality test, homogeneity test, hypothesis test and paired sample test